TRANSLATION THEORY RESEARCH - Sheraliyeva, Shaxnoza (Журнал иностранных языков и лингвистики, 2023)
In our article, taking into account the fact that translation is an exercise that anyone who knows languages ​​​​can do, the author will consider a number of principles that will help translators in their work. Given the difficulty of creating a single general theory of translation, these principles inform the various existing theories of translation and should never be taken too far from the cultures and societies in which translations are performed.